Advertising as a tool to stimulate the sales market of construction company services - N. M. Suray; M. A. Vasilenko (Омский научный вестник: Серия "Общество. История. Современность")
The article studies the role of advertising as a tool to stimulate the market of sales of construction organization services on the example of two large companies: PJSC «PIK C3», LLC «Donstroy». The urgency of this study is due to the constant growth of demand for residential real estate, which requires effective marketing strategies to attract customers. The aim of the work is to analyze the methods and techniques of advertising used by these construction organizations. To achieve this goal, the following tasks are set: to study the features of advertising campaigns of new construction companies of economy class — PJSC «PIK C3» and business class — LLC «Donstroy», to conduct a comparative analysis of their effectiveness, Identify the main strengths and weaknesses of each strategy. The results of the study led to the conclusion that advertising plays a key role in the successful promotion of services of construction organizations in the market. Each company chooses its own unique approach to advertising, taking into account the peculiarities of its target audience and competitive environment.